A comparative study of the proposed ways of creating Iranian music in the written works of Farhad Fakhredini and Sharif Lotfi - Nima Khiali; Hamidreza Dibazar; Ali Mahdaviseresht (هنرهای زیبا. هنرهای نمایشی و موسیقی, 2025)
In recent decades, Iranian composers have engaged in Western classical music composition while also considering the characteristics of Iranian instrumental music. This has led them to develop methods for creating music that incorporate a framework grounded in both Western classical music and Iranian musical traditions. Two notable figures, Farhad Fakhredini, and Sharif Lotfi, have presented strategies for this creative process. By analyzing Fakhredini's books Form and Creation in Iranian Music and Harmony of Iranian Music, alongside Ali Ebrahimi's Basics of Creation in Iranian Music (based on Lotfi’s teachings), we gain valuable insights into these approaches. This research aims to interpret and compare these methods, focusing on the understanding of "creation" in Iranian music. Through library research and interviews with these two composers, this article explores how each of them frames the process of making music in the context of Western and Iranian traditions.Farhad Fakhredini emphasizes creativity in music-making, using the term "creation" to highlight the need for originality. For him, creating music is not merely about following established rules but deeply engaging with the material to produce something unique.  He believes that Iranian music can benefit from adopting Western harmonic and formal principles while retaining its distinct identity. His approach suggests a balance between innovation and tradition, encouraging composers to explore new ideas within Iran’s musical heritage.Sharif Lotfi offers a different perspective in this field. In his approach, he differentiates between "composition" in the Western sense and "creation" in non-Western, particularly Iranian, music. According to Lotfi, Western classical music is characterized by a structured, systematic approach, with form and harmony playing central roles. In contrast, Iranian music creation is seen as a more fluid, spontaneous process, shaped by cultural and aesthetic traditions rather than rigid compositional rules. For Lotfi, "creation" reflects the intuitive nature of Iranian music, rooted in its cultural context. A comparative analysis of these two approaches reveals both similarities and differences in their interpretations of musical creation.Both Fakhredini and Lotfi value Western composition techniques, but they apply them differently. Fakhredini supports a synthesis of Western methods with Iranian music, while Lotfi focuses more on preserving the authenticity of Iranian traditions and emphasizes the philosophical differences between the two systems. The findings of this research highlight how Iranian composers like Fakhredini and Lotfi have developed unique approaches to music creation, drawing from both Iranian traditions and Western techniques. However, they differ in how they integrate these influences. Fakhredini advocates for blending both traditions, while Lotfi prefers to maintain a clearer distinction between them, particularly in his interpretation of "creation" as inherently Iranian. In conclusion, the methods developed by these composers provide valuable insights into the ongoing dialogue between tradition and innovation in Iranian music. By examining their works and interviews, this research sheds light on how they have responded to the challenges of blending Western teachings with Iranian music. Their contributions offer a framework for understanding the complexities of music creation in contemporary Iran and the broader discussion of cultural preservation versus adaptation.